Improving English Speaking Skills using the SmallTalk2Me Artificial Intelligence-Based Tool:: An Innovative Approach in Secondary Education - Jiménez Iñiguez, Camila (2025)
Artificial Intelligence is covering all areas of science and English Language learning is not the exception. Therefore, this study examines how the AI-based tool SmallTalk2Me enhances English-speaking skills among A2-level secondary students in a private high school. Using an exploratory design, pre- and post-intervention assessments re vealed significant improvements in pronunciation and fluency, highlighting the tool's potential for fostering interactive learning environments. Furthermore, students displayed increased confidence and engagement in speaking activities, which fostered a more dynamic learning environment. Therefore, these results highlight the importance of SmallTal k2Me artificial intelligence-based tools in helping to improve speaking skills in a more interactive way.